Everything Old Is New Again: Drug Repurposing Approach for Non-Small Cell Lung Cancer Targeting MAPK Signaling Pathway - Jain, Anisha S.; Prasad, Ashwini; Pradeep, Sushma; Dharmashekar, Chandan; Achar, Raghu Ram; Silina, Ekaterina; Stupin, Victor; Amachawadi, Raghavendra G.; Prasad, Shashanka K.; Pruthvish, R; Syed, Asad; Shivamallu, Chandan; et al. (Frontiers in Oncology, 2021)
Non-small cell lung cancer (NSCLC) is a prominent subtype of lung carcinoma that accounts for the majority of cancer-related deaths globally, and it is responsible for about 80% to 85% of lung cancers. Mitogen-Activated Protein Kinase (MAPK) signaling pathways are a vital aspect of NSCLC, and have aided in the advancement of therapies for this carcinoma. Targeting the Ras/Raf/MEK/ERK pathway is a promising and alternative method in NSCLC treatment, which is highlighted in this review. The introduction of targeted medicines has revolutionized the treatment of patients with this carcinoma. When combined with current systems biology-driven stratagems, repurposing non-cancer drugs into new therapeutic niches presents a cost-effective and efficient technique with enhancing outcomes for discovering novel pharmacological activity. This article highlights the successful cutting-edge techniques while focusing on NSCLC targeted therapies. The ultimate challenge will be integrating these repurposed drugs into the therapeutic regimen of patients affected with NSCLC to potentially increase lung cancer cure rates.